Boosting Building Materials Industry: Strategies for Attracting Foreign Investment: Meningkatkan Industri Bahan Bangunan: Strategi Menarik Investasi Asing. - Uzakova Umida (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article aims to emphasize the importance of establishing effective policies to attract foreign investment and to identify external and internal factors that influence a country's ability to attract foreign investment. By analyzing global experiences in attracting foreign investment, this study outlines the main strategies for increasing investment attractiveness in the economy, with a particular focus on the building materials industry. The research findings suggest that improving infrastructure and regulatory frameworks, implementing favorable tax policies, and promoting transparency and stability are effective ways to increase foreign investment in this industry. The implications of this study indicate that increasing foreign investment can lead to job creation, economic growth, and technology transfer, ultimately contributing to the development of the building materials industry and the overall economy. Highlights: Effective policies are crucial for attracting foreign investment. Factors such as infrastructure, regulation, taxes, transparency, and stability influence a country's ability to attract foreign investment. Increasing foreign investment can lead to job creation, economic growth, and technology transfer. Keywords: foreign investment, investment attractiveness, building materials industry, infrastructure, regulatory frameworks